Հոգեւոր կեցության տեղաշարժերի և գոյաբանական խնդիրների արտացոլումը Մուշեղ Գալշոյանի երկերում - Երվանդյան, Զ.
Темы геноцида и бойнь в начале XX века, насильственного переселения, сражений за независимость, гонений с родной земли, горестных перемещений духовного бытия своего времени довольно ярко представленны в произведениях талантливого писателя Мушега Галшояна.. Как в настоящем, так и в образных воспоминаниях прошлого главный вопрос бытия героев Галшояна связывается с их семьей, домом, родным очагом, так как естественная форма и состояние бытия человека обуславливаются в частности этими понятиями, которые в более широком смысле охватывают понятие родины. По мнению Галшояна потеря родного края способна поколебать не только основы бытия индивидуума, но и целой нации. Именно этому вопросу посвящена данная статья литературоведа З.Ервандян. The themes of battles for gaining a liberty, forced migration, deprivation of the homes in their own country, existential distressing transfers of Galshoyan’s lifetime period, massacres and genocide at the turn of the 20th century are widely represented in the works of the talented writer Mushegh Galshoyan. Both in the present and in the memories of the past the essential existential problem of Galshoyan’s heroes was in connection with their home and family as the natural forms and existence of man are conditioned with these conceptions and widely involve the idea of homeland. According to Galshoyan’s point the loss of them would stagger the existential basis not only of a person, but also of the whole nation. The following article of philologist-specialist in study of literature Z. Yervandyan is dedicated to discussion of the above-mentioned issue in particular.
Keywords: Գրականագիտություն